2019
DOI: 10.1021/acs.iecr.9b03619
|View full text |Cite
|
Sign up to set email alerts
|

Assembling Graphene-Encapsulated Pd/TiO2 Nanosphere with Hierarchical Architecture for High-Performance Visible-Light-Assisted Methanol Electro-Oxidation Material

Abstract: Photoactivated methanol oxidation electrocatalysis attracts broad interest in recent years. Herein, we report the novel reduced graphene oxide encapsulated with a Pd-modified TiO 2 nanosphere (PTG) hierarchical composite by the electrostatic assembly strategy. The homodisperse tiny palladium nanoparticles (Pd NPs) on the TiO 2 support (Pd/ TiO 2 ) ensure more active sites exposed, and graphene encapsulation ensures rapid electron transmission and high light utilization of the PTG material. This tailor-made com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Normally, chronopotentiometry is another method to evaluate the resistance of catalysts to the oxidation of methanol. [36,37] Figure 7B shows the chronopotentiometry curves of Pt-Bi 2 WO 6 /RGO and Pt-Bi 2 WO 6 electrodes under different conditions. It can be observed that the potential increased with the polarization time going on, and then jumped to higher potential rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…Normally, chronopotentiometry is another method to evaluate the resistance of catalysts to the oxidation of methanol. [36,37] Figure 7B shows the chronopotentiometry curves of Pt-Bi 2 WO 6 /RGO and Pt-Bi 2 WO 6 electrodes under different conditions. It can be observed that the potential increased with the polarization time going on, and then jumped to higher potential rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, a graphene-wrapped Pd/TiO 2 sphere (PTG) was prepared according to a previous report. 31 2.4. Electrochemical and Photoelectrochemical Measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work has found that the graphene-encapsulated Pd/ anatase−rutile TiO 2 sphere (PTG) shows the enhanced performance under visible light, and the anatase−rutile phase of TiO 2 and the graphene-wrapped process are essential for the photoassisted MOR due to the sufficient contact between the conductive graphene and the active component. 31 Therefore, it is attractive and meaningful to construct photopromoted MOR catalysts combined with the merits of the core−shell and graphene-encapsulated strategy to boost their catalytic activity and stability. Herein, we designed a novel graphene-wrapped Pd/SiO 2 @ TiO 2 core−shell sphere (PTSG) using a layer-by-layer selfassembly strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The light harvesting of TiO 2 can be affected by its morphology; thus a series of nanostructures such as nanosheet, nanowire, and hollow structure has been developed to boost the photocatalytic performance. In particular, the mesoporous TiO 2 with a hollow structure has drawn a lot of attention because of its more active sites and high surface area, which favor the surface chemical reaction and transportation of electro-active component. , On the other hand, the hollow TiO 2 can adsorb and generate multiple scattering of light, which is beneficial for extension of the light path and enhancement of the light absorption . As for improving the conductivity, the common solution is to combine the TiO 2 with conductive carbon materials such as C/TiO 2 hybrid and graphene/TiO 2 . Especially, it is found that encapsulation of the active material into the graphene largely improved the photoelectrochemical performance, because of which the full contact between active sites and the graphene could maximize the conductive pathways for the transportation of the electron or photogenerated electron charge. , Although some efforts were devoted to fabricate the noble metal/TiO 2 system only restricted to UV light-assisted MOR, ,, the activity and CO tolerance of existing photoactive catalysts are far from behind practical applications demand.…”
Section: Introductionmentioning
confidence: 99%